First record in Argentina of Drepanosiphum oregonense Granovsky (Hemiptera: Aphididae) found on maples (Sapindaceae) - Ortego, Jaime; Olave, Anabel; Mier Durante, Milagros Pilar (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The finding in Argentina of the aphid Drepanosiphum oregonense on "maple tree" Acer pseudoplatanus and A. campestre is reported. This report constitutes the first record of this species and of the genus Drepanosiphum Koch from Argentina and the second one from South America.